Theoretical approaches to liana management: a search for a less harmful method - Sfair, Julia Caram; Rochelle, André Luis Casarin; Van Melis, Juliano; Rezende, Andreia Alves [UNESP]; Weiser, Veridiana de Lara [UNESP]; Martins, Fernando Roberto (Taylor & Francis, 2015)
Lianas can change forest dynamics, slowing down forest regeneration after a perturbation. In these cases, it may be necessary to manage these woody climbers. Our aim was to simulate two management strategies: (1) focusing on abundant liana species and (2) focusing on the largest lianas, and contrast them with the random removal of lianas. We applied mathematical simulations for liana removal in three different vegetation types in southeastern Brazil: a Rainforest, a Seasonal Tropical Forest, and a Woodland Savanna. Using these samples, we performed simulations based on two liana removal procedures and compared them with random removal. We also used regression analysis with quasi-Poisson distribution to test whether larger lianas were aggressive, i.e., if they climbed into many trees. The procedure of cutting larger lianas was as effective as cutting them randomly and proved not to be a good method for liana management. Moreover, most of the lianas climbed into one or two trees, i.e., were not aggressive. Cutting the most abundant lianas proved to be a more effective method than cutting lianas randomly. This method could maintain liana richness and presumably should accelerate forest regeneration.
Keywords: Climber; Forest disturbance; Forest restoration; Liana cutting; Liana infestation; Vine